Literature Review: Pengembangan Obat Herbal Sebagai Agen Antifertilitas Non Fisik - Agung Ayu Indira Aiswari Utara, Anak (Green Publisher Indonesia, 2025)
Herbal medicines, containing active plant ingredients, offer an accessible and affordable option as non-physical antifertility agents. Non-physical antifertility agents are substances or methods that prevent pregnancy without requiring physical intervention such as surgery or mechanical contraceptive devices. The research method was carried out by collecting data from ScienceDirect using the keywords